2017
DOI: 10.31594/commagene.392116
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Pesticides Used in Eskişehir and Kütahya Population Areas of Great Bustard (Otis tarda, Linnaeus, 1758)

Abstract: The habitat of the Great Bustard (Otis tarda, Linnaeus, 1758) in our country, due to the change of agricultural land to the natural and secondary steppe, nowadays constitutes mostly farmland. In addition to the pest control in the field of agriculture and indirectly to get more products from agricultural areas, wide variety of pesticides (Herbicides, Rodenticides, Insecticides, etc.) are used. In this study, it has been aimed to identify what agricultural pesticides are used in the living areas of the species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…The threat factors are reported for the Great Bustard are: human presence and disturbance during agricultural activities especially during the breeding season, pesticide usage, habitat loss due to infrastructural changes such as the construction of village roads and electric transmission lines, leakage hunting, collisions with electric transmission lines, and expansion of irrigation systems used in agriculture (Hellmich & Idaghdour, 2002;Alonso et al, 2005b;Pinto et al, 2005;Sastre et al, 2009;Abdulkarimi et al, 2010;Lemus et al, 2011;Bravo et al, 2012;Horreo et al, 2013;Karataş et al, 2015;Karakaya et al, 2017). The threats mentioned by these authors have been observed in all our fields of study and they affect this species with a high degree of importance.…”
Section: Discussionmentioning
confidence: 99%
“…The threat factors are reported for the Great Bustard are: human presence and disturbance during agricultural activities especially during the breeding season, pesticide usage, habitat loss due to infrastructural changes such as the construction of village roads and electric transmission lines, leakage hunting, collisions with electric transmission lines, and expansion of irrigation systems used in agriculture (Hellmich & Idaghdour, 2002;Alonso et al, 2005b;Pinto et al, 2005;Sastre et al, 2009;Abdulkarimi et al, 2010;Lemus et al, 2011;Bravo et al, 2012;Horreo et al, 2013;Karataş et al, 2015;Karakaya et al, 2017). The threats mentioned by these authors have been observed in all our fields of study and they affect this species with a high degree of importance.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisation in agriculture causes direct mortality through egg and chick loss during harvest (Kılıç and Karakaş 2005, Vadász and Lóránt 2015, Nagy 2018) and provides the opportunity to plough and cultivate hills in the landscape, which were once habitat islands that Great Bustards used as leks (Heunks et al 2001, Karakaş and Akarsu 2009). Pesticide use, which can harm Great Bustards directly (Karakaya et al 2017) and/or indirectly by reducing their food supply (Martín et al 2007) is also a widespread practice in Great Bustard habitats in Turkey (Karakaya et al 2017). A return to a more traditional agricultural scheme, involving a mosaic landscape of fallow land, semi-natural habitat patches, and various kinds of crop (Lane et al 2001), with appropriate compensation for farmers for setting aside land, delayed harvest, and lowered use of pesticides, could help preserve the remaining populations.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisation in agriculture causes direct mortality through egg and chick loss during harvest (Kılıç and Karakaş 2005, Vadász and Lóránt 2015, Nagy 2018) and provides the opportunity to plough and cultivate hills in the landscape, which were once habitat islands that Great Bustards used as leks (Heunks et al 2001, Karakaş andAkarsu 2009). Pesticide use, which can harm Great Bustards directly (Karakaya et al 2017) and/or indirectly by reducing their food supply (Martín et al 2007) is also a widespread practice in Great Bustard habitats in Turkey (Karakaya et al 2017).…”
Section: Threats and Conservation Measuresmentioning
confidence: 99%
“…Общее количество птиц этого вида в мире оценивается в 31000 -36000 особей, что на 34% (диапазон 30 -38%) меньше, чем 16 лет назад . В разных частях ареала происходит снижение численности дрофы в результате антропогенного воздействия (Karakaya et al, 2017;Özgencil et al, 2022). Снижение наблюдалось в девяти из 17 стран с размножающимися популяциями, с самыми высокими значениями в Китае (-90%) и европейской части России (-70%) .…”
unclassified